Algebra
posted by Stella .
√3, 3√3 Write a quadratic equation in the variable X having the given numbers as solutions. Type in standard form ax^2 + bx +c =0

a x ^ 2 + b x + c = a ( x  x1 ) ( x  x2 )
In this case :
x 1 = sq 
a x ^ 2 + b x + c = a ( x  x1 ) ( x  x2 )
a leading coefficient
x1 and x2 roots
In this case :
x 1 =  sqrt ( 3)
x 2 = 3 sqrt ( 3 )
a x ^ 2 + b x + c = a [ ( x  (  sqrt ( 3 ) ) ] * [ ( x  3 sqrt ( 3 ) ) =
a [ ( x + sqrt ( 3 ) ) ] * [ ( x  3 sqrt ( 3 ) ) =
a [ x * x + x * sqrt ( 3 )  3 sqrt ( 3 ) * x  3 * sqrt ( 3 ) * sqrt ( 3 ) ] =
a [ x ^ 2  2 sqrt ( 3 ) x  3 * 3 ] =
a [ x ^ 2  2 sqrt ( 3 ) x  9 ]
a [ x ^ 2  2 sqrt ( 3 ) x  9 ] = 0 Divide both sides by a
x ^ 2  2 sqrt ( 3 ) x  9 = 0 / a
x ^ 2  2 sqrt ( 3 ) x  9 = 0